Financial liberalisation, bureaucratic corruption and economic development - Keith Blackburn; Gonzalo F. Forgues-Puccio (Institute for Advanced Development Studies (INESAD), 2008)
We study the eþect of international financial integration on economic development when the quality of governance may be compromised by corruption. Our analysis is based on a dynamic general equilibrium model of a small economy in which growth is driven by capital accumulation and public policy is administered by government appointed bureaucrats. Corruption may arise due to the opportunity for bureaucrats to embezzle public funds, an opportunity that is made more attractive by financial liberalisation which, at the same time, raises efficiency in capital production. Our main results may be summarised as follows: (1) corruption is always bad for economic development, but its effect is worse if the economy is open than if it is closed; (2) the incidence of corruption may, itself, be affected by both the development and openness of the economy; (3) financial liberalisation is good for development when governance is good, but may be bad for development when governance is bad; and (4) corruption and poverty may co-exist as permanent, rather than just transitory, fixtures of an economy.
Keywords: D73; F36; O11; 330; Corruption; development; financial liberalisation; Kapitalmarktliberalisierung; Entwicklung; Kleines-Land-Modell; Governance-Ansatz; Korruption; Theorie